Constitutional Development and the Role of Democratic Advocacy: The Quo Vadis of General Elections in Indonesia - Anom Suryo Nindito; Rodiyah Rodiyah; Martitah Martitah; Suhadi Suhadi; Edy Sujendro (Universitas Negeri Semarang, 2026)
The implementation of simultaneous national and regional elections in Indonesia in 2019 and 2024 revealed significant constitutional, administrative, and democratic challenges. These included excessive institutional burdens, diminished voter rationality, weakened regional political discourse, and severe humanitarian impacts on election administrators. These conditions culminated in Constitutional Court Decision No. 135/PUU-XXII/2024, which mandates the separation of national and regional elections beginning in 2029. This article critically examines the constitutional direction, democratic implications, and normative risks of this decision, particularly its role as an instrument of constitutional engineering within Indonesia’s presidential system. Employing prescriptive qualitative legal research, the study utilizes doctrinal analysis, comparative constitutional review, and content analysis of legal norms, court decisions, and scholarly literature. The findings indicate that while election separation has the potential to strengthen governability, enhance regional democratic focus, and improve electoral rationality, it simultaneously poses risks of constitutional change by stealth. This could potentially undermine the five-year election principle and democratic legitimacy if not carefully regulated. This research contributes by integrating constitutional law, theories of governability and governmentality, and democratic advocacy into a cohesive analytical framework that moves beyond procedural electoral reform. The study concludes that Constitutional Court Decision No. 135/PUU-XXII/2024 should be treated as a constitutional guideline rather than a substitute for formal amendment. Accordingly, it recommends legislative harmonization of election laws, strengthened civic advocacy, enhanced political education, and cautious institutional restraint to ensure that electoral reform advances substantive democracy without eroding constitutional integrity.